Penerapan Teknik Psikoanalisis Dalam Meningkatkan Interaksi Sosial Klien ODHA - Aulia Raudhotul Jannah; Suryati Suryati; Neni Noviza (Journal of Society Counseling, 2023)
This study entitled "the application of psychoanalytic techniques in increasing the social interaction of PLHIV clients at PKBI Palembang". The purpose of this study was to determine the social interaction of PLHIV clients and to find out psychoanalytic techniques in increasing social interaction with PLHIV clients. This type of research is field research using a qualitative approach with descriptive methods. Data collection techniques using observation, interviews, and documentation. The research subjects included 3 people, namely 2 PLHIV clients who were in PKBI and one PKBI administrator. Miles and Huberman's model combines three data analysis techniques at once, namely data reduction, data presentation, and drawing conclusions or verification. The results of the study were obtained from observations and interviews, 1) a description of the social interactions of PLHIV clients, namely almost having similarities and differences in their answers, for example, some communicate with more than one person and some don't, still have fear in speaking, and some are more received and some have not received. 2) the application of psychoanalytic techniques in increasing social interaction shows that clients are able to increase their social interaction however, not fully because PLHIV still have thoughts of low self-esteem and decreased confidence. Keywords: Psychoanalytic Techniques, Social Interaction, PLHIV